Penyusunan Laporan Keuangan Berdasarkan PSAK 109 Menggunakan Microsoft Excel 2019 Pada Program Sedekah Berjamaah BMKA Salman ITB - Nurul Hasanah; Jouzar Farouq Ishak (Indonesian Accounting Literacy Journal, 2022)
This final project, entitled "Preparation of Financial Statements Based on PSAK 109 Using Microsoft Excel 2019 at BMKA Salman ITB Sedekah Berjamaah Program" is a qualitative study that aims to find out how to compile financial reports in the congregational alms program using Microsoft Excel 2019 and accordance with PSAK 109. The method used in this research is descriptive method. Data was collected through interviews, observation and documentation. The results of this study indicate that the recording of financial statements in this congregational alms program uses Microsoft Word and Excel but is not in accordance with accounting rules and the data collection still needs to be improved. As a solution to these problems, the researchers conducted the preparation and design of financial reports using Microsoft Excel. With the drafting of this financial report, it is hoped that it will facilitate the congregational alms program in making financial reports that are easier to understand and develop.